Currículo da nudez: relações de poder-saber na produção de sexualidade e gênero nas práticas ciberculturais de nude selfie - Luíza Cristina Silva Silva (2018)
The practice of capturing and sharing one's nudity from naked self-portrait contributes to the body, sexuality, gender, and nudity integrating the worldwide network of computers and other digital artifacts. In the practice of self-nude thousands of users display naked self-portraits on digital social networks. This multiplicity of exposed nude bodies published and shared constitute contemporary power relations and ways of fabricating ways of experiencing sexuality and gender in a manner amalgamated with digital technologies. The present text aims to investigate the ways in which the curriculum of nudity works in the production of sexuality and gender relations in cyberculture. In this investigation, the nudity curriculum was researched through the netnography of three secret groups on the social network Facebook. Secret groups exist with the main purpose of exchanging, publishing and playing with naked self-portraits. Online interviews with ten participants of the groups were also carried out to complement and deepen the information production. The analysis of this research was elaborated from a post-critical perspective and the main concepts used are: curriculum as a cultural artifact that is in multiple spaces and unfolding in different pedagogies (PARAÍSO, 2010); gender as "the mechanism by which the notions of masculine and feminine are produced and naturalized, but gender may well be the apparatus by which these terms can be deconstructed and denatured" (BUTLER, 2014, p.253) and sexuality as a historical device constituted by relations of power (FOUCAULT, 2014). The argument developed in this dissertation is that the nudity curriculum consists of powerknowledge relations around gender and sexuality, which act by prescribing adequate, safe and pleasurable forms of existence. Such curricular prescriptions operate both in reiterating social norms and in denouncing and transgressing them. In this sense, at least two positions of subject are produced in these relations locked in the curriculum: cyborg and fruits-of-being-ourselves. These positions are marked by the intimate connection with digital technologies and the transgression of moral imperatives. Cyborgs are taught to be fruit-of-themselves-ones that fruition pleasure, self-esteem and political action from naked self-portrait and thus produce dissident practices to gender norms and sexuality.